SUMBER ILMU PENGETAHUAN DALAM MANAJEMEN PENDIDIKAN - Simbolon, Nursyaidah; Siregar, Agung Kaisar (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2021)
According to language, science consists of two syllables, namely science and science. Science derives from the word 'allama in Arabic is interpreted to taste or signal. While 'Science in Arabic means knowledge. The characteristics of science are, systematically, generality, rationality, objectivity, verifiability and community. Systematic of science is structured like a system that has important facts that are interrelated.The quality of science in general can summarize various phenomena that are ever wider by determining concepts that are increasingly common in the target of discussion. Rationality, based on rational thinking that adheres to the rules of logic. Verifiability, can be checked for correctness, reinvestigated or retested by any other member of the scientific community. Community, generally acceptable, after being tested for truth by scientists. While the object of science can be divided into two parts, namely material objects and formal objects.Â  The source of knowledge consists of empirism (senses), rationalism (reason), intuition (intuition), nationalism (heart) and revelation. How to Acquire Science begins with reason in order to acquire or gain knowledge. Empirical uses reason to form ideas or concepts of objects. Especially in the school of rationalism that emphasizes the ability of reason. Intuition, illumination and revelation are obtained from the power of reason to think. However, the knowledge generated from these sources is different.Â Â